The OEIS Foundation is supported by donations from users of the OEIS and by a grant from the Simons Foundation.

Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 56th year, we are closing in on 350,000 sequences, and we’ve crossed 9,700 citations (which often say “discovered thanks to the OEIS”).

 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A177113 Sequence defined by the recurrence formula a(n+1)=sum(a(p)*a(n-p)+k,p=0..n)+l for n>=1, with here a(0)=1, a(1)=2, k=-2 and l=0. 1
 1, 2, 0, -2, -12, -42, -144, -466, -1476, -4522, -13384, -37794, -99964, -237738, -455104, -366706, 2555276, 20416150, 103683976, 445363518, 1736519252, 6310980502, 21595986320, 69654711278, 210206070236, 581729708502 (list; graph; refs; listen; history; text; internal format)
 OFFSET 0,2 LINKS FORMULA G.f f: f(z)=(1-sqrt(1-4*z*(a(0)-z*a(0)^2+z*a(1)+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z) (k=-2, l=0). Conjecture: +(n+1)*a(n) +(-7*n+2)*a(n-1) +(11*n-13)*a(n-2) +15*(n-4)*a(n-3) +2*(-16*n+65)*a(n-4) +12*(n-5)*a(n-5)=0. - R. J. Mathar, Mar 02 2016 EXAMPLE a(2)=2*1*2-4=0. a(3)=2*1*0-4+2^2-2=-2. a(4)=2*1*(-2)-4+2*2*0-4=-12. MAPLE l:=0: : k := -2 : m:=5:d(0):=2:d(1):=m: for n from 1 to 30 do d(n+1):=sum(d(p)*d(n-p)+k, p=0..n)+l:od : taylor((1-sqrt(1-4*z*(d(0)-z*d(0)^2+z*m+(k+l)*z^2/(1-z)+k*z^2/(1-z)^2)))/(2*z), z=0, 30); seq(d(n), n=0..30); CROSSREFS Cf. A177111. Sequence in context: A122496 A335756 A230813 * A347010 A281205 A285152 Adjacent sequences:  A177110 A177111 A177112 * A177114 A177115 A177116 KEYWORD easy,sign AUTHOR Richard Choulet, May 03 2010 STATUS approved

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recent
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified December 7 20:40 EST 2021. Contains 349589 sequences. (Running on oeis4.)